A Historical Analysis of Chairul Anwar’s Poetries Entitled “Aku” and “Tak Sepadan" - Komang Sathya Yogindra Aditia; Syamsurijal Syamsurijal; Sutarman Sutarman; Agus Syahid; Hilda Hastuti (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study examines the semantic elements in Chairil Anwar’s poems “Aku” and “Tak Sepadan” by applying theories from linguistic semantics. Semantics, as described by Leech (1981), is the study of meaning in language beyond its surface structure. The poems were selected due to their emotional intensity and their reflection of personal and national identity during a time of political upheaval. Using Leech’s classification of meaning, including denotative, connotative, and affective meanings. This study explores how language in Anwar’s poetry functions beyond literal interpretation. The method used is qualitative descriptive, where each line of the poems is analyzed based on its lexical choices and semantic implications. Palmer (1981) states that semantics focuses on how meaning is structured through language, especially in poetic texts where context and association are key to interpretation. The findings reveal that “Aku” expresses resistance and self-assertion through strong connotative expressions, while “Tak Sepadan” uses affective meanings to convey personal loss and emotional disillusionment. This research contributes to understanding how semantic analysis can be applied to Indonesian poetry and offers insight into the historical and ideological contexts embedded in linguistic expression.